Magnetotelluric investigations to identify geothermal source zone near Chabsar hotwater spring site, Ahmedabad, Gujarat, Northwest India. (January 2017) - Mohan, Kapil; Kumar, G. Pavan; Chaudhary, Peush; Choudhary, Virender Kumar; Nagar, Mehul; Khuswaha, Dilip; Patel, Pruthul; Gandhi, Drasti; Rastogi, B.K.
Highlights: Magnetotelluric Survey is conducted to locate possible geothermal source zone at Chabsar hotspring site near Ahmedabad, Gujarat (India). The sediment thickness, deccan trap thickness and basement depth is estimated in the area. The geothermal zone and West Cambay Fault with its dip direction are located in the study area. Abstract: The Cambay graben is one of the known geothermal provinces in the Gujarat state in Western India. Temperatures between 100 and 150 °C have been recorded up to 3.5 km depth in this zone. To understand the geoelectric structure and possible source zone of hot water spring at Chabsar, 50 km southwest of Ahmedabad, on the left bank of Cambay basin, magnetotelluric (MT) investigations have been carried out at 24 sites with inter site spacing of ∼1.5 km along four east-west profiles surrounding the hot water spring. The good quality high frequency MT data has been acquired to better resolve the image of shallow subsurface of the region. The recorded MT time series were processed and earth response functions were estimated in broad frequency range. The two-dimensional (2-D) inversion of the transverse electric (TE) and transverse magnetic (TM) mode data including vertical magnetic field component (Hz) of all four profiles have been performed after distortion and decomposition analysis. Combining 2-D structures of all the four profiles we infer a ∼900 m thick Quaternary and Tertiary sediments overlain on Deccan traps of thickness around 1500 m in the study region. The combined geoelectric structure after integrating the 2-D models of all four profiles shows the presence of a conductive zone (<10 Ω m) at a depth of ∼1.0 km with in traps possibly connected with Western Cambay Fault and extended down to 2–2.5 km in central part of the study area. In view of deepening of basement below the high conductive zone and reported large heat flow values of the Cambay basin, we infer that the zone is presumably filled with fluids which may have a heat source at deeper levels.